Developing a Competency-Based Critical Thinking Skills Training Program for Students of the Vietnam–Japan Program at Ho Chi Minh City University of Technology and Education - Nguyễn Thị Út Duyên; Dương Thị Kim Oanh (Journal of Technical Education Science, 2025)
Critical thinking is an essential skill for students in the context of higher education innovation, especially in international collaborative programs such as the Vietnam–Japan program. However, current training practices at Ho Chi Minh City University of Technology and Education (HCMUTE) show that this skill has not yet been systematically or methodically developed. Based on theoretical foundations of the competency-based approach, established critical thinking competency frameworks, and data derived from a project on soft skills among Vietnam–Japan program students, the research team has developed a critical thinking training program consisting of nine logically sequenced modules ranging from foundational understanding to applied practice. The program is designed to ensure alignment between learning objectives, instructional content, teaching methods, and assessment formats. It places emphasis on building learners’ capacity to analyze and evaluate information, manage diverse arguments, and solve real-world problems using critical reasoning. This study concludes at the program development phase and does not include implementation in real teaching settings. Therefore, its effectiveness in practice has not yet been validated. Future research will focus on experimental implementation to support further refinement and evaluation of the program.